EFEK HOLDING TIME PROSES AKTIVASI TERHADAP STRUKTUR PORI KARBON AKTIF DARI AMPAS KOPI SEDUH - Dewa Putra Negara Dewa; I Made Widiyarta Made; Tjokorda Gde Tirta Nindhia Tjokorda; Anton S Ferdinand Ferdinand (Jurnal Rekayasa Mesin, 2022)
Activated carbon has a high adsorption capacity due to its high porosity. The pore structure of activated carbon is largely affected by the chemical composition of the raw material and the parameters of the manufacturing process. This article aims to determine the pore structure of activated carbon from brewed coffee. The manufacture of activated carbon is carried out in one step of carbonization and activation in the same reactor and furnace. The sample was carbonized by heating to a temperature of 650 ○C, then immediately activated at that temperature by flowing nitrogen with 30, 60, and 90 minutes variations. The resulting activated carbons are marked as K-A30, K-A60, and K-A90 for activation holding times of 30, 60, and 90 minutes, respectively. Then the activated carbon was characterized to determine their proximate composition, morphology, and surface pore structure. The results showed that activated carbon under an activation holding time of 60 minutes (K-A60) had the highest fixed carbon content of 71.67%. Meanwhile, generally, the activated carbon K-A30 has the best pore structure due to it having the highest pore surface area (121.765 m2/g), pore-volume (0.058 cc/g), and nitrogen adsorption capacity (37.692 cc/g) with an average pore diameter of 1.915 nm. This research is urgent because it can convert brewed coffee grounds into activated carbon with such pore structure characteristics and potently applied to various adsorption applications.